EVALUASI PROSES PEMBELAJARAN TEMATIK BERORIENTASI KETERAMPILAN ABAD 21 DI MIN 1 TOLITOLI - Anisa, Anisa (DIRASATUL IBTIDAIYAH, 2024)
This research aims to describe teacher readiness in terms of the availability of learning tools, the description of the 21st-century skills-oriented thematic learning process based on the 2013 curriculum. This type of research is evaluation research with qualitative descriptive data analysis techniques. The subjects of this research were class V students of MIN 1 Tolitoli. The data collection method uses student activity observation sheets oriented toward 21st-century skills and interview guides. The results of the research show that the evaluation results in the planning aspect (antecedent) mean that teachers are ready to carry out the 21st century skills-oriented thematic learning process as seen from the completeness of the equipment owned by the teacher, in the implementation aspect (Transaction), (1) the Critical Thinking process on the observation sheet reaches 80% active with high criteria with a tendency for students to be ready for indicators of focusing questions and building fundamental skill (2) The collaboration process on the observation sheet reaches 80%, which classified as active with high criteria with a tendency for students to be ready for discussion indicators. (3) The communication process on the observation sheet reached 88%, classified as active with high criteria with a tendency for students to be ready for oral and written indicators. (4) The creativity process on the observation sheet reached 75%, classified as active with medium criteria. In terms of outcomes, the learning outcomes of MIN 1 Tolitoli students who are oriented towards 21st-century skills are classified as good. Based on data obtained from 29 students in class V MIN 1 Tolitoli, it is known that students can identify and conclude from the questions given so that the answers to the questions given can be answered well. Keywords: Evaluation; Thematic Learning Based; 21st-Century Skills.